An Instrumental Exploratory Case Study on Educators’ Perceptions of Professional Development for 1:1 Technology Use - LeDune, Chad; Chametzky, Barry (Tauladan Fathimah Azzahra, 2024)
Professional development is necessary for the effective use of technology in the constructivist learning environment. Indiana’s fifth through eighth-grade public educators were not provided adequate professional development on how to use 1:1 technology in a constructivist learning environment. The purpose of this study was to investigate the role professional development plays with 1:1 technology use in the constructivist learning environments of Indiana’s fifth through eighth-grade public classrooms. There was a gap in research related to perceptions of Indiana’s fifth through eighth-grade educators on the role of training for technology implementation in a constructivist learning environment. The technology acceptance model (TAM) and constructivist learning theory (CLT) served as the basis for the theoretical framework. The study’s qualitative data was analyzed through inductive, thematic analysis. Research questions focused on the role of technology in Indiana’s fifth through eighth-grade classrooms and the benefits of professional development for using technology in constructivism. Participants taught core subjects in Indiana’s fifth through eighth-grade classrooms and had three years of teaching experience at a school implementing 1:1 technology. Data collection from 15 educators occurred on Zoom using semi-structured interviews and a focus group. Analysis revealed a lack of district-provided technology training, the advantages and prominent role of technology, its contributions to constructivism, and the prominence of constructivism in the classroom. Future studies could investigate educators beyond Indiana in grades K through 12 and use an alternate theoretical framework such as TPACK.